2013
DOI: 10.1039/c3mb70137a
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of temperature stress-responsive proteins in Arabidopsis thaliana rosette leaves

Abstract: Plants, as sessile organisms, are continuously exposed to temperature changes in the environment. Low and high temperature stresses have a great impact on agricultural productivity, since they significantly alter plant metabolism and physiology. Plant response to temperature stress is a quantitative character, being influenced by the degree of stress, time of exposure, as well as plant adaptation ability; it involves profound cellular changes at the proteomic level. We describe here the quantitative variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 50 publications
5
48
0
Order By: Relevance
“…Similar observations have been reported with herbivorous insects or temperature stress in Arabidopsis plants (Collins et al 2010;Rocco et al 2013). Photosynthesis-related proteins (RuBis carboxylase large chain, oxygen-evolving enhancer protein 1-1, chloroplastic, oxygen-evolving enhancer protein 2-1, chloroplastic, and RuBis carboxylase) were observed in Table 1.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar observations have been reported with herbivorous insects or temperature stress in Arabidopsis plants (Collins et al 2010;Rocco et al 2013). Photosynthesis-related proteins (RuBis carboxylase large chain, oxygen-evolving enhancer protein 1-1, chloroplastic, oxygen-evolving enhancer protein 2-1, chloroplastic, and RuBis carboxylase) were observed in Table 1.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it is indicated that heat stress causes downregulation of different key enzymes of the Calvin cycle in rice, including RuBis carboxylase (Han et al 2009). The expression of RuBis carboxylase large chain was significantly downregulated in Arabidopsis leaves due to heat treatment (Rocco et al 2013). Zou et al (2011) indicated that RuBis carboxylase could be considered as a part of the plant adaptive response, to maintain CO 2 fixation under stress factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example of successful application in plant research, a nanoLC-ESI-MS/MS analysis of proteins in excised spots from gel after two-dimensional electrophoretic purification and digestion of Arabidopsis thaliana leaves (i.e. analysis of small pieces of material) has been published [23].…”
Section: Introductionmentioning
confidence: 99%